Influence of lower extremity joint and foot segment velocities on scoring success in taekwondo electronic body protector - Ryu, S.; Park, S.-K.; Gil, H.-J.; Jang, K. (Korean Journal of Sport Biomechanics, 2025)
Objective: This study aimed to analyze the kinematic differences between scoring-success and scoring-failure roundhouse kicks in Taekwondo and to determine the influence of lower extremity joint angular velocity, foot segment linear velocity, and attack angle of the velocity vector on scoring success against the electronic body protector (EBP). Method: Eleven male Taekwondo athletes (Age: 21.1 ± 0.8 years, Height: 178.7 ± 9.5 cm, Body Weight: 63.8 ± 12.3 kg, Career: 11.1 ± 2.6 years) participated in the study. Each athlete performed ten randomized roundhouse kicks, from which three successful and three unsuccessful scoring attempts were selected for analysis. Three-dimensional motion analysis was conducted using an eight-camera system (120 Hz) and a markerless tracking algorithm. Kinematic variables, including lower extremity joint angular velocities, foot segment linear velocities, and the attack angle of the foot segment velocity vector relative to the opponent's EBP, were calculated across the kicking phase. Paired t-tests and logistic regression analyses were used to examine differences and identify predictors of scoring success. Results: The medio-lateral linear velocity of the foot segment was significantly higher in successful kicks (p < .05). Additionally, the sagittal-plane attack angle of the foot segment velocity vector significantly predicted scoring success (p < .05). Conclusion: These findings indicate that EBP scoring success is influenced more by the foot segment's directional velocity toward the target than by the magnitude of joint angular velocity. The results highlight the importance of precise foot trajectory alignment and directional impact in successful scoring, suggesting that training should emphasize optimized approach paths rather than solely increasing kicking force.